Research-Based Laboratory Promotes Student-Learning Skills and Enhances Undergraduate Research Experience - Choudhary, Madhusudan; Johnson, Hannah (IJRDO- Journal of Educational Research, 2016)
Research experience, at the undergraduate level, is important in understanding the scientific process. However, employment and adaptation of research-based laboratory has been challenging to apply in a large class setting as well as being effective in properly exposing students to core concepts in genetics covered during the lecture. This paper describes how analysis of the ctrA gene, which encodes a master cell-cycle transcriptional regulator for bacterial cell-cycle regulation, was adapted and incorporated into the laboratory component of an undergraduate Introductory Genetics course. A total of 159 students participated in this project over a three-semester period, and was carried out with approval from the Institutional Review Board. The test-instrument consisted of collaborative and critical thinking questions dealing with core principles of genetics. Pre-test and post-test scores were compared to assess studentlearning and overall effectiveness of the proposed curriculum in light of course objectives. The results validate that the research based laboratory approaches not only broadens student-learning skills their understanding of core concepts in genetics, but also provides the necessary technical skills to carry out independent research projects.